Opus Habana, organe du discours urbanistique de l’Oficina del Historiador de la Ciudad de La Habana - Sylvie Mégevand (Caravelle)
Founded in 1996, Opus Habana is the official magazine of the Oficina del Historiador de la Ciudad de La Habana, whose director is Eusebio Leal. This luxurious publication which seeks above all to reach international readers, pretends to retrieve colonial past as well as the city’s cultural and historical memory. Based on cuban and Havana’s idiosyncracy as well as on artistic promotion, Opus Habana claims a modern cosmopolitan vocation while new political and cultural challenges are emerging in Cuba.